Permasalahan dan Tantangan Pasar Modal Syariah di Indonesia - Rahmatillah Rahmatillah (Economic Reviews Journal, 2026)
The presence of Sharia capital market facilitates Muslims and non-Muslims to invest their funds in accordance with the principles of Sharia provide peace and confidence on halal Transactions. With using qualitative descriptive method through literature review, this study can describe the current capital market conditions research results shows that behind the development there are various problems which needs to be completed in order to achieve the target to the maximum. Various kinds of problems such as human resources, lack of literacy or understanding of Sharia capital market is also a big problem in development of Islamic capital market, this will arise a negative perception of Sharia capital market among the community. Therefore there is a challenge for institutions and academics in making a difference typical of the capital market sharia compared to conventional capital markets such as modification or product innovation to facilitate and provide security products in each transaction investors, increasing interest and interest community to utilize capital market products Sharia also need encouraged its implementation.